Bi-Modal Behavior of Gray Cast Iron and Carbon Structural Steel in Accelerated Marine Atmospheric Corrosion [Comportamiento Bi-Modal de Una Fundición Gris y Un Acero Estructural Al Carbono en Corrosión Atmosférica Marina Acelerada] - Sipos-Hrabal, K; Monsalve-Gonzalez, A; Artigas-Abuin, A; Allende-Seco, R (Universidade Federal do Rio de Janeiro, 2017)
According to data gathered in the last Metal Foundry Industrial Production Survey [1], approximately 46% of the industrial production of ferrous alloys is gray-iron. In this context the study of the atmospheric corrosion resistance of gray-iron becomes interesting to asset its useful life when subject to weathering conditions. The studies of gray-iron atmospheric corrosion behavior are scarce due to the fact that it takes long periods of time for its real-time characterization. In order to validate an accelerated atmospheric corrosion test, a gray cast iron [2] and a carbon steel [3] were subjected to a 40 days accelerated testing, that includes wetting in a saline fog chamber, washing and drying [4], measuring the corroded thickness at each exposure time. These results were then compared with those obtained by Southwell et al [5] after 16 years of exposure in a marine environment (Panamá Canal). The re-sult analysis reveals that both materials show a bimodal behavior, in accordance with those results reported by Melchers et al [6, 7, 8 ]. This behavior is characterized by an inflection point in the kinetic curve of corrosion, meanly related to the presence of bacteria in the interphase metal-corrosion products. The fact that the kinetic curve of corroded thickness shows an inflection point, allows the validation of the proposed methodology as a path to evaluate the atmospheric corrosion resistance in a short time test. © 2017, Universidade Federal do Rio de Janeiro. All rights reserved.